Optimized cost effective approach for selection of materialized views in data warehousing - B. Ashadevi (Journal of Computer Science and Technology, 2009)
A data warehouse efficiently processes a given set of queries by utilizing the multiple materialized views. Owing to the constraint on space and maintenance cost, the materialization of all views is unfeasible. One of the critical decisions involved in the process of designing a data warehouse for optimal efficiency, is the materialized views selection. The primary goal of data warehousing is to select a suitable set of views that minimizes the total cost associated with the materialized views. In this paper, we have presented a framework, an optimized version of our previous work, for the selection of views to materialize, for a given storage space constraints, which intends to achieve the best combination of good query response, low query processing cost and low view maintenance cost. All the cost metrics associated with the materialized views selection that comprise the query execution frequencies, base-relation update frequencies, query access costs, view maintenance costs and the system's storage space constraints are considered by this framework. This framework optimizes the maintenance, storage and query processing cost as it selects the most cost effective views to materialize. Thus, an efficient data warehousing system is the outcome.